2016
DOI: 10.1002/joc.4749
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of climate variation indices in Iraq using a statistical factor analysis

Abstract: For over three decades, Iraq has suffered from climate variability and desertification. Rainfall rates have decreased with abnormal high-temperature degrees, recurrence of dust storms has been increasing and many agricultural areas have turned into barren land. In this article, to study these climatic variations and detect important climate indices in Iraq, ten indices (total rainfall, average temperature, maximum temperature, minimum temperature, number of days of dust rising, number of days of dust storm, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Shubbar et al [70] reported that precipitation has decreased over Iraq and it has been accompanied by very high temperature and dust storms especially in summer when temperature higher than 45 • C has been recorded in Baghdad city (the capitol of Iraq) and the southern parts of Iraq. Furthermore, Hoerling et al [39] showed that the winter precipitation has changed toward drier conditions during the period of 1902-2010 in the Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…Shubbar et al [70] reported that precipitation has decreased over Iraq and it has been accompanied by very high temperature and dust storms especially in summer when temperature higher than 45 • C has been recorded in Baghdad city (the capitol of Iraq) and the southern parts of Iraq. Furthermore, Hoerling et al [39] showed that the winter precipitation has changed toward drier conditions during the period of 1902-2010 in the Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Huryai is located in the west of Baghdad, Iraq. It has a climate between continental and subtropical with average annual precipitation of about 213mm per year (Al-Ansari et al, 2014) and average temperatures ranging from 48 C˚ in summer to below 0 C˚ in winter (Shubbar et al, 2016). The site is currently managed with combined sewer systems where both sanitary and storm flow can be disposed.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The main type of precipitation in central Iraq is frontal rainfall from systems that originate in the Mediterranean region during the winter, moving east across northern Iraq before changing to a southerly direction (Shubbar et al ., ). The passage of Mediterranean low pressure systems gives rise to rain during winter and spring, particularly in Baghdad (Iraq), Tehran (Iran) and Amman (Jordan) (Babu et al ., ).…”
Section: Introductionmentioning
confidence: 97%